DETERMINATION OF THE KEY FACTORS THAT INFLUENCE POVERTY THROUGH ECONOMETRIC MODELS - Evgjeni Xhafaj; Ines Nurja (European Scientific Journal, ESJ, 2014)
The purpose of this study is to determinate the most important factors that influence poverty through econometric models that are the logistic regression and the linear log regression. The data are obtained from the Living Standards Measurement Study (LSMS) for 2008 that includes 3600 household interviewed in Albania. At the linear log regression model as dependent variable are the expenditure of consumption of the household per capita and as independent variable (explanatory) are the demographic, educational, zone variables. The logistic regression model has as depended variable the economic status (poor and non poor) and as independent variables are the same mentioned previously. The result of both econometric models confirm that the variables that are strong connected with the expenditure of consumption per capita and with the economic status are: household size, the educational level and gender of the head of household, the zone. This study recommends a carefully review on the reforms to be taken in relation to education in Albania.